Disulfidptosis in tumor progression - Senlin Wan; Changming Liang; Chengwei Wu; Song Wang; Jiawei Wang; Lishuai Xu; Xu Zhang; Yinfen Hou; Yabin Xia; Li Xu; Xiaoxu Huang (Cell Death Discovery)
Abstract Disulfidptosis, a regulated cell death modality driven by the cystine transporter solute carrier family 7 member 11 (SLC7A11), is characterized by actin cytoskeleton collapse under glucose starvation. This review systematically elucidates the pivotal role of disulfidptosis in tumor metabolic reprogramming, with a focus on its molecular mechanisms and distinctions from other cell death pathways. The core mechanisms include SLC7A11-mediated cystine overload and NRF2/c-Myc-regulated pentose phosphate pathway activation. By integrating multiomics data and single-cell transcriptomics, we comprehensively decipher the heterogeneous expression patterns of disulfidptosis-related genes (DRGs) and their dynamic interplay with immune microenvironment remodeling. Furthermore, the coexpression networks of DRGs and disulfidptosis-related long noncoding RNAs (DRLs) offer novel insights into tumor diagnosis, prognosis, and targeted therapy. Therapeutically, SLC7A11 inhibitors (e.g., HG106) and glucose transporter inhibitors (e.g., BAY-876) demonstrate efficacy by exploiting metabolic vulnerabilities, whereas natural compounds synergizing with immune checkpoint blockade provide strategies to counteract immunosuppressive microenvironments. Through interdisciplinary collaboration and clinical translation, disulfidptosis research holds transformative potential in redefining precision oncology.